Moho depths for Antarctica Region by the inversion of ground-based gravity data - Borghi, Alessandra (Zenodo, 2022)
Model for the Antarctica Moho depths based on the database ANTGG2015, that collects gravity data from ground-base, airborne and shipborne campaigns. In this estimate of the Moho depths the contribution of the gravity measures has been maximized reducing any correction of the gravity measures and avoiding constraints of the solution to seismological observations and to geological evidence. It’s a pure gravimetric solution.